Fluids during diagenesis and sulfate vein formation in sediments at Gale crater, Mars. (20th July 2016) - Schwenzer, S. P.; Bridges, J. C.; Wiens, R. C.; Conrad, P. G.; Kelley, S. P.; Leveille, R.; Mangold, N.; Martín‐Torres, J.; McAdam, A.; Newsom, H.; Zorzano, M. P.; Rapin, W.; et al.
Abstract: We model the fluids involved in the alteration processes recorded in the Sheepbed Member mudstones of Yellowknife Bay (YKB), Gale crater, Mars, as revealed by the Mars Science Laboratory Curiosity rover investigations. We compare the Gale crater waters with fluids modeled for shergottites, nakhlites, and the ancient meteorite ALH 84001, as well as rocks analyzed by the Mars Exploration rovers, and with terrestrial ground and surface waters. The aqueous solution present during sediment alteration associated with phyllosilicate formation at Gale was high in Na, K, and Si; had low Mg, Fe, and Al concentrations—relative to terrestrial groundwaters such as the Deccan Traps and other modeled Mars fluids; and had near neutral to alkaline pH. Ca and S species were present in the 10 −3 to 10 −2 concentration range. A fluid local to Gale crater strata produced the alteration products observed by Curiosity and subsequent evaporation of this groundwater‐type fluid formed impure sulfate‐ and silica‐rich deposits—veins or horizons. In a second, separate stage of alteration, partial dissolution of this sulfate‐rich layer in Yellowknife Bay, or beyond, led to the pure sulfate veins observed in YKB. This scenario is analogous to similar processes identified at a terrestrial site in Triassic sediments with gypsum veins of the Mercia Mudstone Group in Watchet Bay, UK.